2021
DOI: 10.1186/s13098-021-00768-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of inulin alleviates metabolism disorders in gestational diabetes mellitus mice via RENT/AKT/IRS/GLUT4 pathway

Abstract: Background Gestational diabetes mellitus (GDM) has significant short and long-term health consequences for both the mother and child. There is limited but suggestive evidence that inulin could improve glucose tolerance during pregnancy. This study assessed the effect of inulin on glucose homeostasis and elucidated the molecular mechanisms underlying the inulin-induced antidiabetic effects during pregnancy. Method Female C57BL/6 mice were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Inulin is a dietary ber that regulates glucose metabolism [23]. The observed reduction in blood insulin content and the consistent levels of glucagon and glucose in this study suggest that inulin attenuates insulin secretion from pancreatic β-cells Miao et al reported that 3.33 and 1.67 g/kg/day inulin supplementation signi cantly reduced blood glucose and insulin levels in gestational diabetes mellitus mice [24]. Similar results were reported by Zhang et al [25]that blood glucose and insulin levels in high-fat mice were signi cantly reduced when supplemented with 2 g/kg of inulin.…”
Section: Discussionsupporting
confidence: 63%
“…Inulin is a dietary ber that regulates glucose metabolism [23]. The observed reduction in blood insulin content and the consistent levels of glucagon and glucose in this study suggest that inulin attenuates insulin secretion from pancreatic β-cells Miao et al reported that 3.33 and 1.67 g/kg/day inulin supplementation signi cantly reduced blood glucose and insulin levels in gestational diabetes mellitus mice [24]. Similar results were reported by Zhang et al [25]that blood glucose and insulin levels in high-fat mice were signi cantly reduced when supplemented with 2 g/kg of inulin.…”
Section: Discussionsupporting
confidence: 63%
“…In human intervention studies, doses ranging from 12 to 16 g/day are often given when testing for metabolic effects of ITF ( Cani et al, 2009 ; Parnell and Reimer, 2009 ; Tarini and Wolever, 2010 ; Rahat-Rozenbloom et al, 2017 ), which equals to 2.46 and 3.33 g/kg body weight in mice, respectively ( Nair and Jacob, 2016 ). In this study, the dose was based on our previously published study of ITF administration in mice ( Miao et al, 2021 ). A high dose was chosen due to the short window of treatment allowed by pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Inulin is a polymer of fructose with a β-(2-1)-glycosidic bond, is low in calories, and can be used as a sugar substitute [ 37 ]. It is also an excellent component of a diabetic diet and was reported to improve glucose and lipid metabolism [ 136 , 137 , 138 ]. Moreover, Rahimiyan-Heravan, Roshangar [ 138 ] reported the potential therapeutic effects of inulin on serum and testicular reproductive markers in diabetic male rats.…”
Section: Discussionmentioning
confidence: 99%